Knowledge based economy –technological perspective: implications and solutions for agility improvement and innovation achievement in higher education - Bogdan Ghilic-Micu; Marinela Mircea; Marian Stoica (Amfiteatru Economic Journal, 2011)
Nowadays, the universities, as driving forces of innovative economy and as components of modern society, based on knowledge and collaboration, face a number of challenges and difficulties. In order to overcome them and to create/ensure the bases of eScience education and research activities, universities have to change culturally, strategically, and operationally. The paper highlights the need for ICT (Information and Communications Technology) use and its implications for higher education. In addition, the study places the theoretical aspects into a specific context, combining technologies through interfunctionality in order to ensure academic education agility and innovation. This involves the use of knowledge, process management, service oriented architectures, and Cloud solutions, exemplifying on the Academy of Economic Studies, Bucharest case. The integrated approach is extended using the SharePoint 2010 platform to improve academic management and achieve harmonization of teaching and research and development content and methods with European Union standards. The platform has been implemented and tested within two AES departments and the Master's Degree Studies in Computer Economics. The results have encouraged the integration of the proposed solution within the institution. The study was based on the authors' competences in the areas addressed and was joined with a rigorous analysis of technology trends and various EU countries (Italy, Germany France, Belgium, Netherlands etc.) universities outputs regarding knowledge economy implications for economic higher education studies.
Keywords: A23; I23; O32; O33; 330; knowledge-based economy; information and communications technology; university studies in economics; university management; agility; innovation; SharePoint 2010